Breeding and embryonic development of Hampala macrolepidota (Van Hasselt and Kuhl, 1823). - Z., Intan K.; Christianus, Annie; Nurul Amin, Sarker Mohammad; Mahmud, Muhamad Hatta (Academic Journals Inc, 2013)
The present study investigated the breeding and embryonic development of sebarau, Hampala macrolepidota from fertilization until early hatched. The matured eggs and sperm were obtained by induced breeding using a commercial hormone, ovaprim. Dosages given for female and male were 0.6 and 0.3 mL ovaprim kg-1 b.wt., respectively. Fertilized eggs were adhesive, spherical and sticky. Fecundity for females weighing 180-280 g ranged from 34,985-75,646 eggs/fish. Average diameter of the fertilized eggs ranged from 0.55±0.13-1.06±0.36 mm. Fertilization rates ranged from 18-28% after 24 h incubation. The observation on the embryonic development covers various stages from newly fertilized eggs, cell division, epiboly, somites until hatched.